Goiânia, 90 anos - Rafael Alves Pinto Junior (Albuquerque (online), 2024)
Resenha do livro: OLIVEIRA, Eliézer Cardoso de; MENDONÇA, Jales Guedes Coelho; CHAUL, Nasr Fayad; JAIME, Nilson. Goiânia, 90 anos. Goiânia: Edições Goiás + 300, 2024. 336 p.